A history of global consumption: 1500-1800 - Baghdiantz McCabe, Ina (Social and cultural history, 2015)
"Examines the history of consumption throughout the early modern period. Takes a chronological and global view to the discussion of evolving consumer practice and culture between 1500 and 1800"--Provided by publisher"--